Patients with Alzheimer's disease and dementia with Lewy bodies mistaken for Creutzfeldt-Jakob disease. Issue 1 (1st July 2001) - Tschampa, H J; Neumann, M; Zerr, I; Henkel, K; Schröter, A; Schulz-Schaeffer, W J; Steinhoff, B J; Kretzschmar, H A; Poser, S
Abstract : OBJECTIVES: To describe the clinical presentation of patients with Alzheimer's disease (AD) or dementia with Lewy bodies (DLB) who were suspected of having Creutzfeldt-Jakob disease (CJD) and to investigate whether current clinical diagnostic criteria cover these atypical forms of AD and DLB. METHODS: Brains from necropsy were examined for the diagnosis of CJD at the German reference centre for spongiform encephalopathies. Symptoms and signs in patients with suspected CJD in whom necropsy showed AD (n=19) or DLB (n=12) were analysed. Their data were compared with a group of patients with CJD (n=25) to determine overlapping and discriminating clinical features. All patients were classified according to clinical diagnostic criteria for CJD, AD, and DLB. RESULTS: Demented patients were suspected of having CJD if disease was rapidly progressing and/or focal neurological signs appeared and/or an EEG showed sharp wave complexes. Myoclonus and limb rigidity were the most common neurological signs in all three dementias. DLB was not suspected in any patient, although patients with DLB showed parkinsonism (58%) and fluctuations (58%). Periodic sharp wave complexes (PSWCs) in EEG typical of CJD were found in five patients with AD and one patient with DLB. 14–3–3 Protein in CSF was detected in 20 patients with CJD, in two patients with AD, but not in any patient with DLB. Although most patients with DLB or AD met the clinical criteria for their respective diagnosis (74% and 90%), they also fulfilled criteria for CJD (42% and 58%). CONCLUSIONS: In patients with rapidly progressive dementia and focal neurological signs, CJD should be the first line diagnosis. Facing the triad dementia, myoclonus, and rigidity, AD should be considered if the disease course is longer and DLB is the differential diagnosis if parkinsonism or fluctuations are present. Findings on EEG or CSF typical of CJD do not exclude AD or DLB.